Regulation Concept of Optimizing Biodiversity Function due to Climate Change through Biological Insurance - Efridani Lubis; Andrean Al Iksan (Journal of Private and Commercial Law, 2023)
Biological diversity, also known as genetic resources, plays a crucial role in sustaining human existence. Despite its significance, the destruction of these resources continues to persist over time, partly due to the impact of climate change. Numerous mechanisms have been implemented at both international and national levels to address this issue. However, the IUCN Red List indicates that the apprehensive situation persists, with 28% (35,765 species) of known species categorized as threatened with extinction as of 2020. In light of this challenge, an alternative worth considering is the concept of biological insurance, wherein biological or genetic resources become objects of insurance in general. Implementing this approach would require careful adjustments and, more importantly, scientific argumentation to support the idea both legally and economically. By employing normative legal research alongside statute and conceptual approaches, it has become evident that the current environmental insurance available in the market does not adequately protect the uniqueness of biological diversity. To strengthen the protection of biological diversity, it is essential to incorporate the sustainable use of natural resources for the prosperity of people while ensuring their sustainability indefinitely. Developing a comprehensive environmental insurance system would involve proposing a specific set of terms and conditions for biological insurance tailored to its unique characteristics. This approach seeks to safeguard and promote the conservation of biological or genetic diversity effectively.